Prevalência de bovinos reagentes à prova de tuberculina no município de Pedro Leopoldo, MG - 1977 - Fernando Cruz Laender (1978)
1072 bovine animals on 60 properties in the county of Pedro Leopoldo, State of Minas Gerais, Brazil, were tuberculinized in order to verify the prevalence of bovine tuberculosis, the influence of manegement practices, and their correlation with the epidemiology of the disease. The tuberculine used was 0,1 m1 bovine P.P.D., containing 5.000 I.U. Initially, the simple cervical intradermal test was used, followd by the comparative cervical intradermal testo n suspect animals, and at the conclusion of the testing, 53 (4,94%) positives and 21 (1,96%) suspects were encountred. The greatest prevalence ocurred in the 4-7 year-age group. In regard to management system, 13% of the positives were completely stabled: 6,3% semi-stabled, and 2,9% were under extensive range management. It was observed that the disease is spread throughout the county and that 51% of the positives originated outside this region. Other factors related to the maintenance and spread of the disease refer to the level of technical assistance given to the farmers (at the farm level), inadequate knowledge of the disease by the farmers, lack of preventive sanitary measures, acquisition of animals without tuberculin testing, precarious and unhygienic installations, deficient feeding practices, and intercurrent debilitating diseases.